PENINGKATAN MUTU MI KERING JAGUNG DENGAN PENERAPAN KONDISI OPTIMUM PROSES DAN PENAMBAHAN MONOGLISERIDA [Quality Improvement of Dried Corn Noodle through the Optimization of Processing Conditions and Addition of Monoglyceride] - . Subarna; Tjahja Muhandri; Budi Nurtama; Antung Sima Firlieyanti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
The objective of this research was to improve the quality of dried corn noodle through the optimization of processing condition using a cooking-forming extruder and the addition of monoglyceride. The process conditions was optimized using Response Surface Methodology (RSM) based on two processing parameters i.e., extruder temperatures (80-90°C) and screw speeds (75-125 rpm). The optimum condition of cooking extrusion was obtained at 90°C and 75 rpm. However, the noodle firmness and stickiness were unsatisfactory. The use of 1% Glyseryl Mono Stearate significantly improved the quality of the noodle with acceptable firmness, elasticity, and elongation. However, the cooking loss and stickiness were still high.